The Role of Organizational Communication in Increasing Employee Work Motivation At PT. Sarana Investindo - Rahmi Aini; Yanti Susila (SEAN Institute, 2023)
The role of communication in an organization is very important, because it will help establish good relationships and good coordination between fellow members in achieving organizational goals, besides that organizational communication will have an impact on increasing the work motivation of the members of the organization. Failure to communicate by PT. Sarana Investindo in the company can cause failure to achieve company goals and risk threatening the existence and good name of the company. This study examines the application of organizational communication at PT. Sarana Investindo to increase employee motivation. The research method used is qualitative-descriptive with a case study approach. Data collection techniques used through observation, interviews, and literature studies The results of the study explain that the role of organizational communication at PT. Sarana Investindo relies on mutual communication between leaders and employees to increase motivation at work, especially to meet physiological needs based on Maslow's theory for employees. From the results of the research team's interviews, the obstacles that the company has are namely: a) technical factors; b) human factors; c) semantic factors; and d) psychological factors. To deal with these obstacles, a. fulfill job satisfaction; b. provide training; and c. supervise, evaluate, and guide leaders.